In vitro mass propagation from shoot tip explants of Vernonia cinerea (L.) Less. - an antioxidant, antiinflammatory medicinal plant - Maharajan, M.; Ahmed, A.B.A.; Taha, R.M.; Jawahar, S.; Ravi Paul, R.; Jayaseelan, M. (2010)
Plantlets were regenerated from the shoot tip explants of Vernonia cinerea (L.) Less. in MS supplimented with BA and Kn. Maximum number of shoots in BA (13.32 mg/l) and roots in IBA (7.38 mg/l) developed. The rooted plantlets were successfully established in the field.